Aspects in the Interdisciplinary Decision-Making for Surgical Intervention in Ulcerative Colitis and its Complications - Brown, J.; Meyer, F.; Klapproth, J.-M. (Zeitschrift für Gastroenterologie, 2012)
Ulcerative colitis (UC) is a chronic inflammation of the large bowel, predominantly affecting young adults of 20 to 30 years of age. Even though the majority of patients with limited and extensive UC can be managed medically, 20 to 30 % will require surgical intervention at some point in their life to gain control of the inflammatory process. The most common reason for urgent and emergency surgery is a lack of response to maximal medical inpatient therapy after five to ten days. Other indications include hemorrhage, free perforation, sepsis, and toxic megacolon. Procedure of choice for the majority of surgeons is open or laparoscopic subtotal colectomy and end ileostomy, with or without exteriorization of the rectal stump. The laparoscopic approach requires more time, but allows for faster return of bowel function and discharge from the hospital. Creation of a definite restoration in form of a J pouch should be delayed for at least three months. Indications for elective surgical intervention include cancer, dysplasia associated lesion or mass, and stricture. Preferably, the J pouch and Brooke ileostomy are performed in two stages, with a takedown of the ileostomy several months later. A single-stage operation is associated with increased anastomotic dehiscence, sepsis, and long-term pouch failure. The laparoscopic creation of a J pouch is largely dependent on the surgeon’s experience, but results in a number of advantages, including faster return of bowel function, tolerance of diet, and discharge. Regardless of emergency, urgent, or elective surgical intervention, early involvement of a team of gastroenterologist, surgeon, nutritionist, and stoma nurse is essential in the management of severe UC to maximize a satisfactory patient outcome.
Keywords: ulcerative colitis; operation; laparoscopic surgery; (sub)total colectomy; pouch; ileostomy